0113 Technical checklists in simulation setup. (2nd November 2015) - Gay, Christopher; Graby, Matthew; Charlton, Olivia; Raina, Anju; Jaworskagrajek, Malgorzata; Riby, Stuart
Abstract : Background/context: It is well established in healthcare that Checklists reduce the reliance on memory and can lead to standardised care. 1 Preparing for a simulation scenario has its parallels with surgery – a wide range of equipment, several concurrent procedures being followed, a constantly shifting staffing pool and a requirement to get it right first time under pressure. The HILS Technical Team piloted the use of a checklist over a mandatory 15 day simulation course to gain evidence of good practise in simulation organisation. Description of innovation or topic: HILS Technical Team already has extensive experience of setting up and supporting simulation scenarios – using this we created a checklist to be followed before starting simulation. The list centred on these three areas Sim Suite – the room in which the delegate will be participating in the scenario Control Room – the room in which a majority of faculty will be controlling the scenario Viewing Room – the room in which the remainder of the delegates will watch the scenario At every opportunity, the scenario was started until the checklist was followed and the technician gave the go ahead. To monitor the results, we logged down how often the checklist was used, whether all elements were checked, and the various negative impacts that occurred, as well as general comments on the perceived use of the checklist by faculty. Improvements/outcomes (anticipated or recorded): Scenarios that used the checklist were less prone to technical issues Adherence to the checklist required leadership skills from technicians at times Some technical problems emerged that were not on the checklist, but could be added for the next version. Take home messages: The benefits of checklists are widespread and thoroughly recommended. Reference: http://www.who.int/patientsafety/safesurgery/checklist/en/